A recurring improvisational methodology for change management in ERP implementation - SIEBER, Michelle (Institutional Knowledge at Singapore Management University, 1999)
Change has become an ongoing phenomenon and business process re-engineering has become a necessity for survival of organizations as we approach the 21st century. As participants in this ever-changing working environment, we must be innovative in managing change as it affects both our professional and personal lives. One of the innovative ways to manage change in the implementation of an enterprise resource planning (ERP) system is to adopt a comprehensive change management methodology. In this research, we propose the use of the recurring improvisational change methodology for managing such change. This research is also aimed at implementing the improvisational change methodology at the University of Nebraska (UN) as it seeks to increase its administrative efficiencies. This paper describes and illustrates how the methodology can be used to manage change in the implementation of SAP R/3 at UN.